2023
DOI: 10.26633/rpsp.2023.48
|View full text |Cite
|
Sign up to set email alerts
|

Colistin resistance in Escherichia coli and Klebsiella pneumoniae in humans and backyard animals in Ecuador

Abstract: Objective. Colistin is an antibiotic of last resort for treating serious Gram-negative bacterial infections. However, the misuse of colistin, especially as an animal growth promoter, has contributed to increasing antimicrobial resistance, mediated mainly through plasmid transfer of the mcr-1 gene. This study assessed the prevalence of phenotypic and molecular colistin resistance in Escherichia coli and Klebsiella pneumoniae in Ecuador in healthy humans and their chickens and pigs. Methods. Fecal samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This level of resistance is also significant, especially considering the widespread occurrence of E. coli and the potential for A. baumannii to cause severe hospital-acquired infections. In E. coli , the Col R levels are often very low as reported at 0.5% in Ecuador from faecal samples of humans, pigs, and chickens [25], although higher levels have been observed in Asian countries [31,32]. A recent meta-analysis reported the prevalence of Col R E. coli in food samples and food-producing animals to be 5.70% [33].…”
Section: Discussionmentioning
confidence: 99%
“…This level of resistance is also significant, especially considering the widespread occurrence of E. coli and the potential for A. baumannii to cause severe hospital-acquired infections. In E. coli , the Col R levels are often very low as reported at 0.5% in Ecuador from faecal samples of humans, pigs, and chickens [25], although higher levels have been observed in Asian countries [31,32]. A recent meta-analysis reported the prevalence of Col R E. coli in food samples and food-producing animals to be 5.70% [33].…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is an urgent need for increased surveillance and epidemiological control to prevent the emergence of antibiotic resistance and implement timely intervention strategies. Low-income rural areas in Latin-American countries, where backyard animal husbandry is prevalent [74], are particularly vulnerable to the spread of antibiotic-resistant pathogens. Of special concern is the presence of several ST identified in this study that have been previously associated with epidemiologically relevant clones in the hospital and non-hospital environments, highlighting the need for further surveillance addressed to control the spread of MDR bacteria and underscores the need for a coordinated One-Health approach to combat the global threat of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ban of colistin use in animal husbandry in Ecuador since 2019, the continuous use of other antibiotics, such as β-lactams in agricultural production, may contribute to the permanent co-harboring of these genes in animal and human carriers [74]. This, in turn, increases the risk of zoonotic transmission of resistant bacteria from animals to humans, given the close coexistence between humans and backyard animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ecuador, Ortega-Paredes et al reported the first clinical isolate of colistin-resistant Escherichia coli harboring mcr -1 in 2016 [ 12 ]. Since then, mcr -1 in E. coli and Klebsiella pneumoniae has been described in Ecuador in animals from rural farms [ 13 ]. Therefore, this study aimed to assess the epidemiology and risk factors associated with colistin-resistant carbapenemase-producing Enterobacterales (CR-CPE) and describe the mortality in a low-income country.…”
Section: Introductionmentioning
confidence: 99%